find -Ln(1-e(i[tex]\theta[/tex]) (in terms of theta)
(this is me just skipping the part of the problem I know and going straight to what I can't figure out)
ln(z) = ln(rei[tex]\theta[/tex])=Ln(r) + ln(ei[tex]\theta[/tex]) = Ln(r) + i[tex]\theta[/tex]
The Attempt at a Solution
I don't really know how to break this logarithm up into real and complex parts, the two ways I considered were
= -(Ln(1-1) + i[tex]\theta[/tex])
but that ends up with Ln(0) which blows up to infinity and doesn't make sense in this problem.
= -(Ln(1) + i[tex]\theta[/tex])
but this is just -i[tex]\theta[/tex] which leaves only an imaginary part, and the problem implies there is a real logarithmic solution as well.